2020
DOI: 10.1111/psyg.12636
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mild behavioural impairment: a systematic review and meta‐analysis

Abstract: Aim Mild behavioural impairment (MBI) is a neurobehavioural syndrome characterized by emergent neuropsychiatric symptoms in later life. There has been no systematic review or meta‐analysis on the prevalence of MBI. The main aim of the study is to calculate the pooled prevalence of MBI. Methods A search of the literature on MBI in mild cognitive impairment (MCI), cognitively normal (CN), and subjective cognitive impairment (SCI) and CN but at risk (CN‐AR) subjects published between 1 January 2003 and 28 Septemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…FTD is commonly misdiagnosed in non‐specialist settings 34 and incident cases occurring after age 65 years are rare 35 . Similarly, personality changes and neuropsychiatric symptoms are common precursors to dementia, 36,37 which creates some uncertainty about the diagnostic accuracy of personality disorder and other mental disorders during the pre‐index dementia diagnosis. Also, the data used to estimate SMRs were based on mortality patterns from January 1, 2011, to December 31, 2016, which was a period marked by increasing US suicide rates for males and females aged 65 to 74 years, 7 and may not generalize to other epochs.…”
Section: Discussionmentioning
confidence: 99%
“…FTD is commonly misdiagnosed in non‐specialist settings 34 and incident cases occurring after age 65 years are rare 35 . Similarly, personality changes and neuropsychiatric symptoms are common precursors to dementia, 36,37 which creates some uncertainty about the diagnostic accuracy of personality disorder and other mental disorders during the pre‐index dementia diagnosis. Also, the data used to estimate SMRs were based on mortality patterns from January 1, 2011, to December 31, 2016, which was a period marked by increasing US suicide rates for males and females aged 65 to 74 years, 7 and may not generalize to other epochs.…”
Section: Discussionmentioning
confidence: 99%
“…Further, this syndrome has already been recognized in the community and in clinical research cases and has been shown to be present not only in many older patients with sustained neuropsychiatric symptoms or MCI but also in some cognitively normal older adults [ 79 - 82 ]. A recent a systematic review and meta-analysis based on 11 studies including 15,689 subjects (older adults) has showed that the pooled prevalence of MBI was 33.5% (95% confidence interval: 22.6%-46.6%) [ 83 ]. Additionally, 18.2% of the older adults without dementia were found to have MBI [ 84 ].…”
Section: The Relationship Between Depression and Dementiamentioning
confidence: 99%
“…The MBI‐C is a 34‐item questionnaire, providing information on later life emergent symptoms and behaviours that have been present for at least 6 months, as described in the MBI criteria. MBI is common among cognitively normal (CN), subjective cognitive impairment (SCI), and MCI subjects, with a pooled prevalence of 17%, 35.8%, and 45.5%, respectively according to a recent meta‐analysis incorporating various case ascertainment approaches 19 …”
Section: Introductionmentioning
confidence: 99%